Teaching English to students studying music: Integrative approaches and pedagogical strategies in ESP classrooms - Akbarova, Moxichexra Rifatillayevna (The Lingua Spectrum, 2026)
This article examines contemporary approaches to teaching English to students specializing in music and highlights the role of integrative pedagogical strategies in developing their professional competence. The study emphasizes the practical value of musical terminology, authentic texts, song lyrics, performer interviews, concert reviews, listening tasks, and communicative activities in the English classroom. Particular attention is paid to English for Specific Purposes methodology, which allows music students to learn English through materials directly connected with their future professional activity. The article argues that music-based English lessons create a meaningful, motivating, and practice-oriented learning environment where students can connect language acquisition with artistic expression. The findings indicate that integrating English language teaching with music education expands students’ professional vocabulary, improves listening and speaking skills, and enhances their ability to participate in international musical communication, academic exchange, performances, and creative collaboration. Thus, English becomes not merely an academic subject, but an essential instrument of professional, intercultural, and artistic communication for future musicians.